2007
DOI: 10.1002/hec.1297
|View full text |Cite
|
Sign up to set email alerts
|

Use of evidence in economic decision models: practical issues and methodological challenges

Abstract: SUMMARYThis paper outlines the current 'state of play' regarding the use of evidence in decision modelling and highlights both practical issues and methodological challenges related to identifying, combining and reporting evidence to inform decision model parameters and structure. Based on discussions at two MRC HSRC-funded workshops consisting of 37 experts from a range of disciplines (i.e. decision-makers, health economists, information specialists, operations researchers and statisticians), it aims to deriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(61 citation statements)
references
References 24 publications
0
57
0
4
Order By: Relevance
“…60 However, the identification of all relevant evidence is very demanding and most search strategies practised lack uniformity and transparency. 124 There are no clear guidelines on this process and a recent review of modelling guidelines reported inconsistent advice. 59 This methodological issue has been recognised and more guidance on searches for model parameters is anticipated.…”
Section: Cost-effectiveness Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…60 However, the identification of all relevant evidence is very demanding and most search strategies practised lack uniformity and transparency. 124 There are no clear guidelines on this process and a recent review of modelling guidelines reported inconsistent advice. 59 This methodological issue has been recognised and more guidance on searches for model parameters is anticipated.…”
Section: Cost-effectiveness Methodsmentioning
confidence: 99%
“…Possible data sources have been categorised as research based, real world based and reference based. 118,124 Research-based sources of evidence include RCTs, meta-analyses of RCTs, observational studies and economic models. Examples of real-world data sources are administrative databases, hospital or other health-care statistics and disease registers.…”
Section: Evidence Used In Decision Modelsmentioning
confidence: 99%
“…Within health economics, however, while there have been significant advances in evidence synthesis methods based on decision analytic modelling (Ades et al, 2006;Cooper et al, 2007;Weinstein, 2006), and a key book on the role of systematic reviews and health economics was published in 2002 (Donaldson et al, 2002a), this debate has been comparatively limited. Nevertheless, systematic reviews of economic studies have become a key feature of many policy making and technology assessment processes, and also a common form of published study in certain health economics journals.…”
Section: Introductionmentioning
confidence: 98%
“…Moreover, if a drug is effective, a cost-effectiveness analysis at the population level could be used to synthesise the data from multiple cohorts and trials into a form that is more explicit for decision makers (Cooper et al 2007). In such a model, factors like cost, demographics, the availability of appropriate tests, the incidence of toxoplasmosis infection in pregnant women and of clinical symptoms in children must be taken into consideration to evaluate future options and recommendations (Ades 2005, personal communication at the EuroTOXO consensus conference).…”
Section: How To Inform Future Trials and Recommendations?mentioning
confidence: 99%